Invasive potential of the Peruvian pepper tree (Schinus molle) in South Africa - Midoko Iponga, Donald (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Conservation Ecology and Entomology))--University of Stellenbosch, 2009.